A Chatbot-supported Smart Wireless Interactive Healthcare System for Weight Control and Health Promotion - Huang, Chin-Yuan; Yang, Ming-Chin; Huang, Chin-Yu; Chen, Yu-Jui; Wu, Meng-Lin; Chen, Kai-Wen (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
People who are overweight and obese have a greater risk of developing serious diseases and health conditions. A steadily increasing trend of obesity is not only limited to developed countries, but to developing nations as well. As smartphones have rapidly gained mainstream popularity, mobile applications (apps) are used in public health as intervention to keep track of diets, activity as well as weight, which is deemed more accurate than relying on user's self-report measure, for the sake of weight management. A solution called "Smart Wireless Interactive Healthcare System" (SWITCHes) is developed to facilitate objective data reception and transmission in a real-time manner. Based on the user data acquired from SWITCHes app and the auxiliary data from medical instruments, not only SWITCHes app can engage user with tailored feedback in an interactive way, in terms of artificial intelligence-powered health chatbot, but the healthcare professional can provide the more accurate medical advice to user also. This paper presents an overview of development and implementation of SWITCHes.